The impact of institutional factors and IFRS on the value relevance of accounting information: Evidence from ah shares / Zou Feng - Zou , Feng (2021)
The study investigates whether institutional factors affect the value relevance of accounting information of Chinese cross-listed firms during the years 2000 to 2013. It covers the last two sets of China's accounting standards – both the Accounting System for Business Enterprises (ASBE) released in 2001 and the revised version in 2006. Specifically, the study concentrates on whether the IFRS convergence is associated with the incremental improvement on the value relevance of accounting information, and how the institutional factors affect the value relevance of these cross-listed firms. It is now well established from various studies that IFRS convergence would improve the corporate disclosure transparency and significantly enhance the quality of accounting information, especially the value relevance of accounting information. However, in the process of global convergence to IFRS, some studies found that institutional factors play a prominent role in affecting value relevance, particularly in emerging economies. Mainland China is communist and led by a one-party political system, while as an inalienable part of China, Hong Kong retains its financial system, legal system, and possesses its own currency. In this respect, the unique situation of Mainland China and Hong Kong embodies the principle of “one country, two systems” and enables the coexistence of socialism and capitalism in the same country. Therefore, because of these institutional differences, it might be expected that the value relevance of accounting information is different between Mainland China and Hong Kong listed firms. Furthermore, to create a side-by-side comparison, firms with twin listing of A-share and H-share are selected as the study sample. These Chinese cross-listed firms issue A-share can also issue H-share, and they are known as AH- shares. To take a close look at the mean differences in theses AH- shares between the pre- and post- IFRS convergence period, the study uses paired sample t-test where the time segment is divided into two equal periods. The result of the study indicates that IFRS convergence could indeed promote higher quality of accounting information, as the value relevance increases when firms switched from complying with the China GAAP to the IFRS-based accounting standards. Besides, the impact of institutional factors on the value relevance has been proved to be varied between Mainland China and Hong Kong stock market. This result suggests that regions with a strong and sound institutional framework and higher scores of the Worldwide Governance Indicators further support and enhance the neutrality of accounting information. Accordingly, such regions would correspond to a lower interventionist power in the financial reporting system and attract more investments. The study also shows that the IFRS convergence has successfully reduced the information asymmetry among Chinese cross-listed shares. In addition, the result finds that all six institutional factors (voice and accountability, political stability and absence of violence/terrorism, government effectiveness, regulatory quality, rule of law and control of corruption) are statistically significant in Mainland China, whereas only two (voice and accountability, regulatory quality) have been confirmed in Hong Kong.